Lambeth Palace : 1. the cloisters : 2. entrance to Lambeth Palace : 3. doorway leading from chapel : 4. crypt under the chapel : 5. entrance to cloisters : 6. garden front of Lambeth Palace - Prior, William Henry (Tufts Archival Research Center, 2006)
This illustration is from Edward Walford "Old and new London, a narrative of its history, its people, and its places, vol. 6"